A novel approach for fabricating adjustable zero field-modulus magnetorheological elastomer based on IPN matrix. (21st August 2019) - Song, Xincheng; Wang, Wenju; Yang, Fufeng; Wang, Guoping; Rui, Xiaoting
Abstract: Toughening modification of magnetorheological elastomer (MRE) is crucial necessity for developing intelligent MRE based devices. To prepare high performance MRE, the thermoplastic elastomer styrene-ethylene butylene-styrene triblock copolymer (SEBS) was added into polybutadiene rubber (BR) to prepare BR/SEBS interpenetrating network (IPN) matrix based MRE. The anisotropic samples were prepared by different vulcanization method under a magnetic field. The mechanical properties of MRE was measured by rheometer. The experimental results showed that the zero-field modulus of MRE was increased with the addition of SEBS. The measurement result of dynamic thermomechanical analysis (DMA) showed that the two-phase heterogeneous system was formed in matrix. The zero-field modulus of this MRE can be adjusted by the content of SEBS and vulcanization time and temperature since the SEBS does not participate in the vulcanization reactions and possess fluidity at high temperature. The MRE with adjustable zero-field modulus have promising advantages in the application of adaptive tuned vibration absorbers.